Bone mesenchymal stem cell-derived extracellular vesicles deliver microRNA-23b to alleviate spinal cord injury by targeting toll-like receptor TLR4 and inhibiting NF-κB pathway activation. Issue 1 (1st January 2021) - Nie, Hongfei; Jiang, Zhensong
ABSTRACT: Bone mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) are known for recovery of injured tissues. We investigated the possible mechanism of BMSC-EVs in spinal cord injury (SCI). EVs were isolated from BMSCs and injected into SCI rats to evaluate the recovery of hindlimb motor function. The spinal cord tissue was stained after modeling to analyze spinal cord structure and inflammatory cell infiltration and detect microRNA (miR)-23b expression. The activity of lipopolysaccharide (LPS)-induced BV2 inflammatory cells was detected. The protein contents of interleukin (IL)-6, IL-1β, IL-10 and tumor necrosis factor-α (TNF-α) in spinal cord and BV2 cells were measured. Western blot analysis was used to detect the level of toll-like receptor (TLR)4, p65, p-p65, iNOS, and Arg1 in spinal cord tissue and cells. TLR4 was overexpressed in rats and cells to evaluate the content of inflammatory cytokines. After EV treatment, the motor function of SCI rats was improved, SCI was relieved, and miR-23b expression was increased. After treatment with EV-miR-23b, iNOS, IL-6, IL-1β, and TNF-α contents were decreased, while Arg1 and IL-10 were increased. The levels of TLR4 and p-p65 in spinal cord and BV2 cells were decreased. The rescue experiments verified that after overexpression of TLR4, the activity of BV2 cells was decreased, the contents of IL-6, IL-1β, TNF-α, and p-p65 were increased, IL-10 was decreased, and SCI was aggravated. To conclude, The miR-23b delivered by BMSC-EVs targets TLR4 and inhibits the activation of NF-κB pathway, relieves the inflammatory response, so as to improve SCI in rats.